2022
DOI: 10.3390/antiox11061192
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory and Cytotoxic Activity of Phenolic Compound Family Extracted from Raspberries (Rubus idaeus): A General Review

Abstract: Raspberries (Rubus idaeus) possess a wide phenolic family profile; this serves the role of self-protection for the plant. Interest in these compounds have significantly increased, since they have been classified as nutraceuticals due to the positive health effects provided to consumers. Extensive chemical, in vitro and in vivo studies have been performed to prove and validate these benefits and their possible applications as an aid when treating several chronic degenerative diseases, characterized by oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 120 publications
(151 reference statements)
0
40
0
Order By: Relevance
“…However, it is not only anthocyanins of blackberry extract that may exert anti-inflammatory activity. Other phenolic compounds and terpenoids have also demonstrated their potential in the inhibition of the inflammation process and the secretion of pro-inflammatory cytokines [ 17 , 75 , 76 ]. Therefore it might be possible that the anti-inflammatory activity demonstrated by blackberry extract was the result of the synergistic effects of various phytochemicals naturally present in blackberry fruits.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not only anthocyanins of blackberry extract that may exert anti-inflammatory activity. Other phenolic compounds and terpenoids have also demonstrated their potential in the inhibition of the inflammation process and the secretion of pro-inflammatory cytokines [ 17 , 75 , 76 ]. Therefore it might be possible that the anti-inflammatory activity demonstrated by blackberry extract was the result of the synergistic effects of various phytochemicals naturally present in blackberry fruits.…”
Section: Resultsmentioning
confidence: 99%
“…To cope with the oxidative stress created by ROS and RNS, antioxidant defenses need to be strong. Phenolic compounds are known to have antioxidant and anti-inflammatory capacities and many studies have shown that phenolic compounds have a scavenging effect on free radicals [ 25 , 26 ]. In addition, they have been extensively studied in recent years, as they exhibit a wide variety of physiological properties such as anti-mutagenic, anti-carcinogenic, and antimicrobial activity [ 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the concentration of polyphenols can increase in response to oxidative stress caused by various factors, such as pests, diseases, ultraviolet light, low temperatures, soil nutrients, and drought [ 83 , 84 ]. Our results for antioxidant capacity are consistent with those and other studies conducted on the same berries species collected in the Ecuadorian Andean region [ 4 , 54 ].…”
Section: Discussionmentioning
confidence: 99%